2013
DOI: 10.1016/j.jiph.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-adherence to antiretroviral therapy in Yaounde: Prevalence, determinants and the concordance of two screening criteria

Abstract: Non-adherence to ART remains high in this population. The careful evaluation of patients for the presence of determinants of non-adherence identified in this study may aid ART optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
3
35
0
2
Order By: Relevance
“…Significant proportions of HIV/AIDS patients attending the care do not reach high levels of adherence leading to viral resistance to the drug. A study done in Yaoundé, Cameroon in 2013 showed that the prevalence of nonadherence to antiretroviral therapy was 34.9% (18). A study done in Nigeria in 2008 found that the prevalence of non-adherence to antiretroviral therapy among adult person living with HIV/AIDS was 37.1% [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant proportions of HIV/AIDS patients attending the care do not reach high levels of adherence leading to viral resistance to the drug. A study done in Yaoundé, Cameroon in 2013 showed that the prevalence of nonadherence to antiretroviral therapy was 34.9% (18). A study done in Nigeria in 2008 found that the prevalence of non-adherence to antiretroviral therapy among adult person living with HIV/AIDS was 37.1% [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study done in northwest Ethiopia in 2010 indicated that the prevalence of nonadherence was 17.3% [16]. A study done in Nigeria in 2008 found thatantiretroviral therapy was 34.9% [18]. These rates of non adherence can contribute to sub-optimal drug levels which can lead to drug resistance and increase mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The ATC of YJH has been described in details previously [13,14]. In brief, YJH is the referral centre for tuberculosis and chest diseases for Yaounde, the Capital City of Cameroon.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Interviewees report an increasing number of patients defaulting treatment because some Pentecostal churches in Namibia encourage their congregations to stop taking medication against HIV and other diseases. 'Born again' religion was recently described as a barrier to adherence to ART in other African countries [19,31], but has not yet been the subject of medical research in Namibia. It is a significant finding of this study that the practices of Pentecostal churches may compromise TB therapy and ART in Namibia.…”
Section: Barriers At the Patient/community Levelmentioning
confidence: 99%